Adolescent females, coercive practices and sexual choice in the era of HIV/AIDS - Noorbhai, Najeebah Yousuf (My University, 2009)
One of the population groups most acutely infected and affected by HIV/AIDS are adolescent females. Coercive practices and gender inequalities have been cited as important determinants of women’s HIV risk. This research aims to explore adolescent girls’ understanding of their identity and heterosexual sexuality. In addition, this study intends to assess the implications that gendered powered relations held for understanding the risks and dilemmas that young women are confronted with in relation to HIV/AIDS contraction. This research presents the findings of a qualitative and quantitative study conducted using a self-constructed questionnaire that was administered to a purposive sample of adolescent girls aged 13-18. Content analysis is used to analyse the data, the aim being to extract themes as they emerged from the data. Some of the following themes were identified as significant in the girls’ responses: The physical changes that occur during adolescence were highlighted alongside the viewpoint that adolescence is a time of inconsistency and turmoil. Self-worth was closely linked and related to socially desirable characteristics, and in addition gendered behaviour was widely endorsed amongst these girls. Romantic relationships were an important component of these girls’ lives. However, many described their relationships as being less sexual and more emotional in nature. The awareness of sexual readiness and choice hold positive implications for HIV/AIDS. A common consensus existed regarding practicing safe sex and almost all respondents agreed that the onset of sexual intercourse should be postponed until the age of 18 years or older. It appeared that although adhering to feminine stereotyped behaviour could be protective in the sense that it may result in less risky sexual engagement, it however, was also apparent that it could render females less powerful within their heterosexual relationships, thereby increasing their vulnerability to HIV infection. Although only a small proportion of the respondents experienced being forced into a sexual encounter against their will, an underlying fear of sexual coercion or threat nevertheless, emerged. It is concluded that sex education should engage with gender-stereotyped behaviour especially during early and middle adolescence when identities are being formed and developed.
Keywords: adolescent females; HIV/AIDS; sexual choice; coercive practices